Flares during long‐term entecavir therapy in chronic hepatitis B. Issue 11 (November 2016) - Chi, Heng; Arends, Pauline; Reijnders, Jurriën G P; Carey, Ivana; Brown, Ashley; Fasano, Massimo; Mutimer, David; Deterding, Katja; Oo, Ye H; Petersen, Jörg; van Bommel, Florian; de Knegt, Robert J; et al.
Abstract: Background and Aim: The incidence and consequences of flares during first‐line nucleos(t)ide analogue therapy are largely unknown. We aimed to investigate the incidence and outcome of alanine aminotransferase (ALT) flares during long‐term entecavir (ETV) in chronic hepatitis B (CHB). Methods: CHB patients treated with ETV monotherapy from 11 European centers were studied. Flare was defined as > 3× increase in ALT compared with baseline or lowest on‐treatment level and an absolute ALT > 3× ULN. Flares were designated as host‐induced (preceded by hepatitis B virus (HBV)‐DNA decline), virus‐induced (HBV‐DNA increase), or indeterminate (stable HBV‐DNA). Results: Seven hundred and twenty‐nine patients were treated with ETV for median of 3.5 years. Thirty patients developed a flare with cumulative incidence of 6.3% at year 5. Baseline hepatitis B e antigen (HBeAg)‐positivity (HR 2.84; P  = 0.005) and high HBV‐DNA (Hazard ratio (HR) 1.30; P  = 0.003) predicted flares. There were 12 (40%) host‐induced, 7 (23%) virus‐induced, and 11 (37%) indeterminate flares. Host‐induced flares occurred earlier than virus‐induced (median: 15 vs 83 weeks; P  = 0.027) or indeterminate flares (15 vs 109 weeks; P  = 0.011). Host‐induced flares were associated with biochemical remission, and HBeAg ( n  = 3) and hepatitis B surface antigen ( n  = 2) seroconversions were exclusively observed among patients with these flares. Virus‐induced flares were associated with ETV resistance ( n  = 2) and non‐compliance ( n  = 1). Conclusion: The incidence of ALT flares during ETV was low in this real‐life cohort. ETV can be safely continued in patients with host‐induced flares. Treatment adherence and drug resistance must be assessed in patients with virus‐induced flares.